Phytochemicals, Nutritional and Anti-Nutritional Composition of Aqueous Extracts of White and Red Onions Bulbs - Abubakar, Ibrahim; Aliyu, Jabir Danyaya; Mohammed, Abdulganiyu Galadima; Ibrahim, Iklima Bandi; Sani, Said Said; Umar, Sanusi Farouq (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Onion bulbs have been consumed for foods and nutrition and management of many diseases including infections, diabetes, gastrointestinal disorders, cardiovascular and respiratory disorders. This study aims to evaluate the phytochemicals, nutritional and anti-nutritional composition of the aqueous extracts of white and red onions bulbs. Analytical techniques AOAC and AAS were used in phytochemicals and proximate analysis and determination of minerals, heavy metals, determination of anti-nutrients content of the aqueous extracts of white and red onions bulbs. The findings showed the presence of alkaloids, flavonoids, tannins, glycosides, saponins, steroids, cardiac glycosides, and anthraquinones in the aqueous extracts of red and white onions bulbs. The aqueous extracts of white and red onions bulbs contain significant (p < 0.05) amounts of moisture (89.68 and 87.04%), ash (3.22 and 2.03%), fiber (3.00 and 2.00%), carbohydrates (2.33 and 2.59%), proteins (3.19 and 1.04%), and crude lipids (1.22 and 2.66%), respectively. The aqueous extracts of white and red onions bulbs demonstrated significant (p < 0.05) level of potassium (987.10 and 756.24 ppm), sodium (42.50 and 32.50 ppm), calcium (8.90 and 6.10 ppm), phosphorus (3.87 and 4.04 ppm), zinc (2.32 and 1.13 ppm), magnesium (1.85 and 1.12 ppm), iron (0.62 and 0.58 ppm), and copper (0.47 and 0.17 ppm), respectively. Low concentrations of nickel (0.112 and 0.524 ppm), lead (0.034 and 0.023 ppm), cadmium (0.029 and 0.014 ppm), and chromiun (0.090 and 0.032 ppm) were observed in the aqueous extracts of white and red onions bulbs contain, respectively. The aqueous extracts of white and red onions bulbs exhibited moderate and low amounts of cynogenic glycosides (3.00 and 12.46 mg/100g), saponins (2.02 and 2.07 mg/100g), oxalate (0.63 and 3.75 mg/100g), tannins (0.90 and 1.09 mg/100g), and phytate (0.38 and 1.49 mg/100g), respectively. The aqueous extracts of white and red onions bulbs contain various phytochemicals and significant amounts of important nutrients with trace quantity of certain heavy metals and anti-nutrients.